Impulsiveness and Emotional Dysregulation as Stable Features in Borderline Personality Disorder Outpatients Over Time. Issue 9 (September 2020) - Martino, Francesca; Gammino, Lorenzo; Sanza, Michele; Berardi, Domenico; Pacetti, Monica; Sanniti, Alice; Tangerini, Giulia; Menchetti, Marco
Abstract : Abstract: Large-scale longitudinal studies show that specific borderline personality disorder (BPD) symptoms are more likely to remit over time, suggesting that clinical features of BPD may vary between younger patients and older ones. The objective of the present report is to provide a direct comparison between younger (age 18–25 years; n = 44) and older (age 40–59 years; n = 49) BPD patients on the nine DSM-4 BPD criteria (self-harm, emotional dysregulation, impulsiveness, and work and social functioning). Younger and older patients reported similar levels of impulsiveness, emotional dysregulation, and work and social functional impairment. Younger adults were more likely to show anger and self-damaging behaviors compared with older patients, which in turn were more likely to endorse chronic emptiness. In conclusion, older patients with BPD are still impaired in impulsiveness, emotional regulation, and social functioning; treatments for older BPD population should be long term and focused on emotion dysregulation and impulsive behaviors.